Implementasi Nilai-nilai Pendidikan Multikultural di SMA Nasional 3 Bahasa Putera Harapan Purwokerto (Pu Hua School) - Hani, Tri Nur (Matan: Journal of Islam and Muslim Society, 2020)
The purpose of this study is to present how the implementation of multicultural education in Putera Harapan Purwokerto (Pu Hua School) National 3 High School. Where this school has a policy as a place that accommodates students from various backgrounds both ethnic, religious, racial, cultural, and linguistic. This multicultural, multireligion, and multilingual school is very interesting to be used as a model for applying multicultural education in educational institutions and by the plurality of Indonesian society. The results of this study indicate that: 1) The implementation of multicultural education in Putera Harapan Purwokerto (Pu Hua School) 3 National High School has fulfilled the five dimensions of multicultural education concepts including Content Integration, Construction Knowledge, Prejudice Reduction, Equity Paedagogy, and Empowering School Culture and Social Culture: 2) In the agenda of activities compiled and implemented in the National High School 3 Language of Putera Harapan Purwokerto (Pu Hua School) contains multicultural education values ??consisting of the values ??of Democracy, Humanism values, and the value of Plularism; 3) In the application stage of multicultural education in the National High School 3 Languages ??Putera Harapan Purwokerto (Pu Hua School) is included in the implementation of the Transformation approach where at this level students can have a point of view, see concepts, issues, themes, and problems from several perspectives and points of view ethnicity. They can compete, argue with each other, and start daring to see things from a different perspective.